Development of fuzzy algorithms for the control of the grocery department of the sugar factory - Сокол, Ростислав Михайлович; Смітюх, Ярослав Володимирович (Eastern-European Journal of Enterprise Technologies, 2015)
The automation problem of the grocery department of the sugar factory using intelligent control systems, the variety of which is fuzzy modeling was considered in the paper. In contrast to the classical control methods, fuzzy modeling is the most useful when in the technical system description there is uncertainty that complicates or eliminates the use of precise quantitative methods and approaches. To analyze the functioning of the grocery department as a complex dynamic control system, IDEF0 methodology was applied. Using IDEF0 diagrams has allowed to identify the main controlling and managing variables of the fillmass boiling process in the A-vacuum pan. A set of factors that affect the implementation of simple management purposes was defined. These factors influence the vacuum pan operating modes and A-fillmass boiling process optimization. Linguistic approximation of membership functions of defined variables was conducted, and their variation ranges taking into account expert information obtained as a result of the expert survey were determined. Based on the membership functions, the knowledge base, which is a fuzzy scenario model was built. Based on the knowledge base, fuzzy logic surfaces that allow to assess the inferencing algorithm adjustment and the vacuum pan control adequacy were obtained. The resulting fuzzy model for the vacuum pan control will allow to significantly improve the regulation indicators compared with the classical system. These indicators include reducing the overcontrol and transient process time, taking into account uncertainties and adequate response to disturbance.